Functioning Peculiarities of Argot Vocabulary in the Novel “Fox” by Myroslav Dochynets (Linguostylistic Studies, 2019)
The article argues that social transformations in the last decades have actively influenced the language issues. The vocabulary and semantic system have expanded the resources of the language emotional and evaluative means, mainly at the expense of slang vocabulary. The study focuses on the functioning features of the argot vocabulary in the novel “Fox” by Myroslav Dochynets since it is the basic lexical stratum used in communication by the criminal world in the novel. The author considers important issues of the argot vocabulary life, its entry into the canvas of a work of art, its compliance with stylistic and aesthetic norms. The key findings of the study argue that creative originality is determined by the author's focus on the unusual language of his characters, his desire to convey their world outlook and philosophy by means of argot lexicon, and thus to draw attention of the reader. On the one hand, negative lexical nominations prevail (musora, slidak, kent, shushval, chuika). On the other hand, the author appeals to national language experience of a reader and achieves desired semantic and stylistic effect using units of lexical, phraseological, syntactic language levels. The author analyzes contextual synonyms which emphasize the local coloring of the individual narration: koroidka; vypravna colonia; terytoria, de zakon vidpochyvav; nevilnyi svit; dorosla zona. The study sheds light on the processes that take place in the literary language and assumes the need to evaluate all the components of the speech stream, including the dynamics of the Ukrainian argot system development. The conducted research proves that the language of the criminal world is constantly changing, developing, expanding the sphere of influence and use in fiction, that is, the language develops not in its traditional hypostasis, but in oral, spontaneous, socially uncontrolled speech. Thus, jargon is an element of the linguistic picture of the world, a powerful semiosphere of a particular time layer of culture, which opens a meaningful perspective in the word as a quintessence of the socio-cultural, spiritual, and psychological climate of the epoch.
Keywords: social dialect; jargon; argot vocabulary; sub-code; communication; semio- sphere